MANAJEMEN LINGKUNGAN HOTEL DI BALI: PENERAPAN KONSEP EKOLOGI DALAM KEGIATAN HOTEL - Hajjah, Fajriyatul; Decelle, F. Xavier (Jurnal Ilmiah Pariwisata, 2012)
Current environmental issues to the attention of the world community. Some are concerned with improving the environment directly and pass it to the wider environment. There also appear indifferent and let the damage occurred is getting worse. Not too except Bali, an island famous for its natural beauty, religious traditions and also not spared from destruction and pollution of the environment. It is also not free from the rapidly growing tourism activities. Water and air pollution, land use, coastal erosion, coral reef damage, infrastructure damage caused by various loads in excess capacity and waste disposal continue to rise in place, selokan, rivers and even new - this new litter on the beach of Kuta, causing negative impact on the image of Bali as a tourist destination.Based on the background of the problem that the writer take the topic of environmental management hotels in Bali with text applications of ecological concepts in the activities of the hotel. Hotels that serve the object of study consist of four hotels in the area of ??Seminyak, Jimbaran and Ubud. Of these four hotels, sub-section under study is about the use of land and forests, water, energy, building concept, the use of local products, waste management, environmental and social.And based on the results of research and interviews with practitioners of tourism in Bali that the concept of ecology has not been fully implemented, but the hotel was trying to meet the applicable standards. What matters is how, the participation of all stakeholders including civil society and government in supporting the implementation of these concepts with clear rules and firm.
Keywords: Environment, Ecology, Hotel